2017
DOI: 10.2337/dc16-2753
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Breakfast on Clock Gene Expression and Postprandial Glycemia in Healthy Individuals and Individuals With Diabetes: A Randomized Clinical Trial

Abstract: Breakfast consumption acutely affects clock and clock-controlled gene expression leading to normal oscillation. Breakfast skipping adversely affects clock and clock-controlled gene expression and is correlated with increased postprandial glycemic response in both healthy individuals and individuals with diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
160
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(164 citation statements)
references
References 39 publications
4
160
0
Order By: Relevance
“…42,137,161,193 One exciting and rapidly developing field, based on the understanding that the feeding time represents the most potent Zeitgeber for peripheral oscillators that orchestrate body metabolism, is chrononutrition. 202 Furthermore, recent evidence suggests that timed exercise has the potential to improve metabolic characteristics. [196][197][198][199][200][201] In addition, breakfast consumption or omission has an important impact on body metabolism, in particular in diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…42,137,161,193 One exciting and rapidly developing field, based on the understanding that the feeding time represents the most potent Zeitgeber for peripheral oscillators that orchestrate body metabolism, is chrononutrition. 202 Furthermore, recent evidence suggests that timed exercise has the potential to improve metabolic characteristics. [196][197][198][199][200][201] In addition, breakfast consumption or omission has an important impact on body metabolism, in particular in diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to significantly increasing the risk of obesity, a recent study observed that acute breakfast omission altered clock genes expression and resulted in an increased postprandial glycaemic response (Jakubowicz et al . ). Additionally, shift workers are predisposed to weight gain and metabolic disorders, which has been suggested to arise from circadian misalignment (Antunes et al .…”
Section: Timing Of Eating (Calorie Distribution): Effects On Energy Bmentioning
confidence: 97%
“…; Jakubowicz et al . , ). Humans are a diurnal species with the light cycle stimulating wakefulness and feeding, and darkness initiating sleeping and fasting (Fig.…”
Section: Timing Of Eating (Calorie Distribution): Effects On Energy Bmentioning
confidence: 99%
See 2 more Smart Citations